Pengaruh Program Sekolah Adiwiyata Terhadap Perilaku Peduli Lingkungan Siswa Di SDN KIP Maccini Kota Makassar - Ira Irviana (STKIP Andi Matappa Pangkep, 2021)
This study aims to determine: (1) what is the description of the Adiwiyata program at SD KIP Maccini, Makassar City (2) How to describe the environmental care behavior of students at SD KIP Maccini Makassar City (3) how to describe the influence of the Adiwiyata school program on students' environmental care behavior. This type of research is ex post facto research. The population is 283 students. Sampling using random sampling technique as many as 75 students. The instrument used was a questionnaire on students 'perceptions about the Adiwiyata program and a questionnaire on students' environmental care behavior. The description of the implementation of the Adiwiayata program at SD KIP Maccini Makassar City can be seen that some respondents stated the level of influence of the Adiwiyata program on environmental caring behavior of students in SD. KIP Maccini Makassar city is always 42.67%, followed by the frequent category 26.67% while in the occasional category 20% and never 10.67% category. Hypothesis testing uses inferential statistics to determine the correlation of each variable. The relationship between students 'perceptions and students' environmental care behavior is in the strong category with a correlation of 0.799.